Effects of anesthetic tetradecenols on phosphatidylcholine phase transitions. Implications for the mechanism of the bilayer pretransition. - O'Leary, T J (1986)
The effects of cis- and trans-9,10-tetradecenols on the phase transitions of dimyristoyl-, dipalmitoyl-, and distearoyl-phosphatidylcholines were investigated using high sensitivity scanning calorimetry and Raman spectroscopy. Both alcohols lowered the gel to liquid crystalline phase transition temperatures for all three phosphatidylcholines, with cis-tetradecenol showing a considerably greater effect than trans-tetradecenol in each case. While both alcohols increased the temperature of the dimyristoylphosphatidylcholine pretransition, and decreased the temperature of the distearoylphosphatidylcholine pretransition, cis-tetradecenol lowered the temperature of the dipalmitoylphosphatidylcholine pretransition, while trans-tetradecenol dramatically raised the pretransition temperature. These results are interpreted in terms of the reduction in gel (L beta) phase chain tilt and changes in the ease of acyl chain trans-gauche isomerization which are introduced by the alcohols, and the consequent effects of these changes on the pretransition and the gel to liquid crystalline phase transition. The data clearly show that caution is necessary in applying information on lipid-anesthetic interactions obtained from model membranes to the problem of clinical anesthesia, since qualitatively different results may be obtained when lipids of differing acyl chain lengths are employed. Superficial interpretation of such data might lead to erroneous conclusions.